1989
DOI: 10.1212/wnl.39.2.265
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multiple sclerosis in Lanzarote (Canary Islands)

Abstract: In the island of Lanzarote of the Province of Las Palmas, which is part of the Spanish archipelago of the Canary Islands, the prevalence of multiple sclerosis is 15 per 100,000. The prevalence of MS in Lanzarote seems related more to ethnic conditions than to geography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 0 publications
0
11
1
Order By: Relevance
“…The higher numbers in our study, compared to those previously reported for the same province in the eighties [20,21], can also be explained by both the methodology employed with comprehensive case ascertainment and the higher grade of sanitary development (MR available from 1991). Also, the longer survival of MS patients may play a role.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The higher numbers in our study, compared to those previously reported for the same province in the eighties [20,21], can also be explained by both the methodology employed with comprehensive case ascertainment and the higher grade of sanitary development (MR available from 1991). Also, the longer survival of MS patients may play a role.…”
Section: Discussioncontrasting
confidence: 59%
“…Both studies were performed in a short time period (1 year) and evaluated mainly hospitalized patients [20,21]. A more recent survey conducted in La Palma Island (81,507 inhabitants), using multiple case-ascertainment sources, yielded a higher rate (42 cases/100,000 inhabitants), still lower than that in the Iberian peninsula [22].…”
Section: Introductionmentioning
confidence: 99%
“…This prevalence was higher than that found on other islands in the Archipelago in previously published studies and in which only hospital records were used [11,12]. The clinical features of the disease determine that its prevalence is lower than its real incidence as most benign cases are not detected or they are detected late.…”
Section: Discussionmentioning
confidence: 58%
“…In the Canary Islands, two prevalence studies of MS have been published [11,12]. In the first study carried out on the Island of Gran Canaria, a prevalence of 6.2 cases /100,000 was obtained [11], and later on the Island of Lanzarote, it was 15/100,000 [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation